Model for improvement of occupational health and safety in micro and small construction enterprises - Savić, Dušica; Mučenski, Vladimir; Velkovski, Trajče; Topalić Marković, Jovana; Hadžistević, Miodrag; Šešlija, Miloš (Informa UK Limited, 2022)
This article presents research on qualitative parameters conducted in order to develop a model for the improvement of occupational health and safety (OHS) in micro and small construction enterprises (MSEs). Identification of factors and defining their significance enables improvements of OHS in the observed enterprises. The aim of the model is to assist MSEs in evaluating their qualities, pinpointing their deficiencies and ways to maximize the improvement of OHS performances. A panel of 20 experts defined the factors through an iterative process using the Delphi method. The research resulted in a model consisting of 42 OHS factors grouped into 10 categories. Model validation was carried out in the Republic of Serbia. The validation confirmed the applicability of the model as well as the relevance of factors that were determined by the panel of experts.
Keywords: Delphi method; evaluation; Risk; Model; Occupational safety and health